2009
DOI: 10.1074/jbc.m109.038257
|View full text |Cite
|
Sign up to set email alerts
|

A Caenorhabditis elegans Glycolipid-binding Galectin Functions in Host Defense against Bacterial Infection

Abstract: Galectins are a family of ␤-galactoside-binding proteins that are widely found among animal species and that regulate diverse biological phenomena. To study the biological function of glycolipid-binding galectins, we purified recombinant Caenorhabditis elegans galectins (LEC-1-11) and studied their binding to C. elegans glycolipids. We found that LEC-8 binds to glycolipids in C. elegans through carbohydrate recognition. It has been reported that Cry5B-producing Bacillus thuringiensis strains can infect C. eleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…2C, lanes 2-4). The main glycolipid bands were observed in positions similar to those reported previously (12,16). TLC overlay staining of upper phase glycolipids with MOA revealed binding to N2 and bre-2(ye31) but not bre-4(ye27) glycolipids (Fig.…”
Section: Moa Inhibits C Elegans Development and Amoebal Growthsupporting
confidence: 82%
See 2 more Smart Citations
“…2C, lanes 2-4). The main glycolipid bands were observed in positions similar to those reported previously (12,16). TLC overlay staining of upper phase glycolipids with MOA revealed binding to N2 and bre-2(ye31) but not bre-4(ye27) glycolipids (Fig.…”
Section: Moa Inhibits C Elegans Development and Amoebal Growthsupporting
confidence: 82%
“…This is consistent with MOA susceptibility of N2 and bre-2(ye31) worms and resistance of bre-4(ye27) animals. To identify the glycolipid species that is recognized by MOA, comparative overlay staining with t-Cry5B as described by Ideo et al (12) was performed. The pattern of the orcinol staining and the t-Cry5B overlay of N2-derived glycolipids (Fig.…”
Section: Moa Inhibits C Elegans Development and Amoebal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…3B) that does not contain Galβ1-4Fuc epitope (27). In addition, although LEC-1 has affinity for the chemically Since LEC-1 could bind to glycans containing Galβ1-3GalNAc disaccharide such as Galβ1-3GalNAcβ1-4Galβ1-4Glc (note that this is asialo-GM1 structure found in glycolipid of vertebrate species, while it has not been found in C. elegans glycolipid) (17), a potential endogenous ligand of LEC-1 might be C. elegans Oglycans containing Galβ1-3GalNAc (31, 32) (Fig.…”
Section: Endogenous Ligand Glycans Of C Elegans Galectinsmentioning
confidence: 99%
“…Other groups of researchers have suggested that lec-8 is involved in resistance to bacterial infection. 25,26) It will be necessary to combine the results of the 3 different approaches described above to understand the functions of galectins in C. elegans in vivo. The K a and K d values for the interaction between LEC-12 and the pyridylaminated oligosaccharides were calculated as described in Materials and Methods.…”
Section: )mentioning
confidence: 99%